1993
DOI: 10.1093/mutage/8.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of micronuclei in oral mucosa of users of tobacco products singly or in various combinations

Abstract: Frequencies of micronucleated cells (MNCs) were analyzed in the exfoliated buccal mucosa of normal healthy individuals from different parts of India who were regularly using either areca nut alone, mava, tamol, tobacco with lime, dry snuff or masheri. The analyses were also carried out among oral submucous fibrosis patients who had the habit of chewing either mava or areca nut. Compared with 'no habit' healthy individuals, all the groups, irrespective of their type of habit, had significantly higher frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
2
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 0 publications
1
26
2
2
Order By: Relevance
“…This means that at the same age men have a greater number of MN than women. The previous studies indicate that MN in buccal cells show no differences between sexes [Kayal et al, 1993;Gómez-Arroyo et al, 2000]. Thus, the increases observed could be due to a sum of different factors (e.g., drinking, smoking) not uniformly distributed between sexes.…”
Section: Discussionmentioning
confidence: 81%
“…This means that at the same age men have a greater number of MN than women. The previous studies indicate that MN in buccal cells show no differences between sexes [Kayal et al, 1993;Gómez-Arroyo et al, 2000]. Thus, the increases observed could be due to a sum of different factors (e.g., drinking, smoking) not uniformly distributed between sexes.…”
Section: Discussionmentioning
confidence: 81%
“…The data presented by Wu et al [10] revealed that cigarette smoking did not increase the number of micronuclei in smokers when compared with controls. Kayal et al [11] investigated micronuclei in buccal mucosa cells of persons who chewed indigenous products (areca nut, mava, tamol, tobacco with lime, dry snuff, or mashery), but not tobacco cigarettes. Motgi et al [12] have demonstrated that total numbers of micronucleated cells were significantly lower in non-tobacco users when compared with tobacco users, but such data were obtained by using non-specific DNA stains (Papanicolaou stain).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of epithelial tissue, effective techniques have not yet been developed for preparing metaphase chromosomes for conventional aberration analysis. The MN assay, however, is an effective method for detecting chromosomal aberrations in exfoliated epithelial cells [Tolbert et al, 1992;Kayal et al, 1993;Pastor et al, 2001;Huvinen et al, 2002;Guzman et al, 2003].…”
Section: Introductionmentioning
confidence: 99%